2010
DOI: 10.1021/jp105805w
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Defects on Thermal Decomposition of HMX via ReaxFF Molecular Dynamics Simulations

Abstract: Effects of molecular vacancies on the decomposition mechanisms and reaction dynamics of condensed-phase β-HMX at various temperatures were studied using ReaxFF molecular dynamics simulations. Results show that three primary initial decomposition mechanisms, namely, N-NO(2) bond dissociation, HONO elimination, and concerted ring fission, exist at both high and lower temperatures. The contribution of the three mechanisms to the initial decomposition of HMX is influenced by molecular vacancies, and the effects va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
88
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(101 citation statements)
references
References 42 publications
(51 reference statements)
11
88
2
Order By: Relevance
“…Here the amount of NO 2 reached a maximum of about 9 ps and then started to decrease, indicating that some secondary reactions are already occurring in the CL-20 system. After this point one can expect, a quick consumption of NO 2 molecules with a faster production of stable reaction products, such as N 2 , H 2 O, and CO 2 , as shown in our previous cook-off simulations 26,32 .…”
Section: Shear Under High Pressuresupporting
confidence: 63%
“…Here the amount of NO 2 reached a maximum of about 9 ps and then started to decrease, indicating that some secondary reactions are already occurring in the CL-20 system. After this point one can expect, a quick consumption of NO 2 molecules with a faster production of stable reaction products, such as N 2 , H 2 O, and CO 2 , as shown in our previous cook-off simulations 26,32 .…”
Section: Shear Under High Pressuresupporting
confidence: 63%
“…This is because similar ReaxFF reactive force fields for other materials have been validated to predict accurately both the reactivity of bonds and mechanical properties of condensed phases. 16,[22][23][24][25][26][27][28][29][30][31] The studies of anisotropic sensitivity of PETN and HMX, 16,24 thermal decomposition of HMX (cyclotetramethylene tetranitramine), TATB (triamino-trinitrobenzene), and RDX, [25][26][27] shock dynamics of RDX and PBX (plastic bonded explosives), [28][29][30][31] and so forth using ReaxFF-RMD lead to the results in accordance with available experimental data, making it practical to describe chemical reactions occurring under various conditions during the large scale dynamical processes involving millions of atoms with currently available computational facilities.…”
Section: Introductionmentioning
confidence: 99%
“…8a and b). Zhou et al 3 found that the molecular vacancies accelerate the decomposition of HMX by increasing the reaction rate constant and reducing activation barriers. The VBM of (001)/[010] TB_2 is contributed by both the aNO 2 and eNO 2 groups, while the CBM is contributed dominantly by the aNO 2 groups.…”
Section: Electronic Structuresmentioning
confidence: 99%